Study on Screening tests among the Blood donors in Community Based Medical College Hospital, Mymensingh, Bangladesh (Community Based Medical Journal, 2019)
The aim of the study was to find out the prevalence of transfusion transmitted diseases (TTD) in voluntary and Replacement donors. A total of 4,885 donors were analyzed for the prevalence of TTD over a period of 1 year and 9 month from August 2016 to May 2018, Conducted at the Community Based Medical College Hospital, Mymensingh, Bangladesh, of these 38.8% were voluntary donors and 61.2% were replacement donors. Prevalence of Hepatitis B virus (HBv) was highest (.86%) followed by syphilis (.3%), HCV (.14%), Malaria (.06%) and HIV (.04%). Prevalence was more in male replacement donors. Seropositivity of TTD of this study was much lower among blood donors due to proper medical assessment of donors. Pre-donation donor screening procedures is helpful in improving the blood safety and reduces the prevalence of transfusion transmitted diseases.CBMJ 2019 January: vol. 08 no. 01 P: 19-22